2007
DOI: 10.1002/cjoc.200790100
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Melatonin in Rat Pineal Gland and Drug with Flow‐Injection Chemiluminescence

Abstract: A flow-injection chemiluminescence (CL) method for the determination of melatonin based on the CL reaction of melatonin with hydrogen peroxide and sodium hypochlorite (NaOCl) in a basic alkaline solution was developed. The possible CL mechanism has been discussed, and a proposal for the reaction pathway was given that singlet oxygen was clarified to be produced in this reaction system and was responsible for the CL emission. Under the optimized conditions, the linear concentration range of application was 1.0×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Similar results have also been reported by Wei et al following in vitro research on the interactions of gatifloxacin mesylate compounds (antibiotics from the fluoroquinolone class) and Mitoxantron (anti-tumour drug) with the DNA. It has been concluded that the masking of the fluorescent signal is due to an intercalation process of the studied compounds inside the DNA double strand [30]. The linearity of the graphs obtained in the assessment of the indoles-DNA interactions and the Stern-Volmer constants values reveal the existence of a single fluorophore agent, namely the indole molecules, in the analysed samples and prove the existence of a direct connection between DNA and the studied bio-indoles, as well as the affinity thereof for the formation of specific bonds with the DNA structure, process followed by the quenching of the samples' fluorescence.…”
Section: Dynamics Of Dna-indoles Interaction Processes Depending On the Employed Dna-indole Molar Ratiomentioning
confidence: 98%
See 2 more Smart Citations
“…Similar results have also been reported by Wei et al following in vitro research on the interactions of gatifloxacin mesylate compounds (antibiotics from the fluoroquinolone class) and Mitoxantron (anti-tumour drug) with the DNA. It has been concluded that the masking of the fluorescent signal is due to an intercalation process of the studied compounds inside the DNA double strand [30]. The linearity of the graphs obtained in the assessment of the indoles-DNA interactions and the Stern-Volmer constants values reveal the existence of a single fluorophore agent, namely the indole molecules, in the analysed samples and prove the existence of a direct connection between DNA and the studied bio-indoles, as well as the affinity thereof for the formation of specific bonds with the DNA structure, process followed by the quenching of the samples' fluorescence.…”
Section: Dynamics Of Dna-indoles Interaction Processes Depending On the Employed Dna-indole Molar Ratiomentioning
confidence: 98%
“…The fluorescence quenching is a process which decreases the intensity of the fluorescent signal issued by the analysed sample. The literature describes 2 major processes of fluorescence quenching that can also take place simultaneously in the same sample: dynamic fluorescence quenching and static fluorescence quenching [30,32]. The dynamic fluorescence quenching is due to a diffusion process between the fluorophore agent (indole molecules) and the molecules triggering the florescence quenching (DNA).…”
Section: Dynamics Of Dna-indoles Interaction Processes Depending On the Employed Dna-indole Molar Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Chemiluminescence (CL), which owns excellent sensitivity, wide linear dynamic range and requires relatively simple and inexpensive instrumentation, is a powerful analytical technique. [15][16][17] Nowadays, the CL has been applied to the determination of rifampicin. Li et al 18 made use of continuous-flow chemiluminescence with artificial neural network calibration to carry out the simultaneous determination of the rifampicin and isoniazid, but both the relative standard errors and the detection limit were not satisfactory.…”
Section: Introductionmentioning
confidence: 99%